Assessing the Political Impact of Women’s Political Representation on Women’s Health in Indonesia, 2009-2023 - Meutia May Oryza; Adhi Cahya Fahadayna (MUWAZAH : jurnal kajian gender, 2024)
This study explores the influence of women's representation in the Indonesian Parliament (DPR RI) on women's health outcomes, specifically through the mediation of health policies. The primary objective is to assess whether increased political representation of women leads to improved health conditions for women by influencing policy decisions. The research adopts a quantitative approach, utilizing path analysis using Stata over 15 years. The model examines the relationship between women's representation as the exogenous variable, women's health policies as the intervening variable, and various indicators of women's health as the endogenous variable. Of the 14 health equations analyzed, only two yielded significant results: (1) a direct effect of women's political representation on women's health and (2) a direct effect of women's representation on the coverage of health insurance in Indonesia. The limited significance of these results is attributed to the fact that the 30% gender quota in Parliament has not been fully achieved, and the indicators used to measure women's health may not be fully representative. The study underscores the need for a more balanced representation of women in legislative bodies and the development of more comprehensive health indicators to capture the state of women's health in Indonesia.